Current and potential targets for drug design in the androgen receptor pathway for prostate cancer. (3rd June 2018) - Guddati, Achuta Kumar
ABSTRACT: Introduction : Modulating the androgen axis by different agents has been one of the most successful therapeutic interventions in the field of prostate cancer therapy. Newer agents such as abiraterone and enzalutamide have been widely adapted and have contributed to an increase in the overall survival of prostate cancer patients. However, most of these patients will develop resistance to these agents and will need chemotherapy. Areas covered : In this review, this author discusses current agents which modulate the androgen axis, the mechanisms of resistance to these agents and investigative agents which are designed to bypass these mechanisms of resistance. Potential targets in the androgen axis and related biochemical pathways are, furthermore, identified. Expert opinion : Understanding the mechanism of resistance to these agents is crucial in developing third generation anti-androgen agents which can potentially contribute to the longevity of prostate cancer patients to a greater extent. Besides developing more potent agents, it is also important to formulate new strategies to resensitize patients to current anti-androgen agents by carefully sequencing chemotherapy regimens and abrogating genetic changes which are known to cause resistance to anti-androgens. Combinatorial approach with immunotherapy offers prospects which may yield better results and need to be thoroughly explored.